Racial differences in weathering and its associations with psychosocial stress: The CARDIA study - Sarah Forrester; David Jacobs; Rachel Zmora; Pamela Schreiner; Veronique Roger; Catarina I. Kiefe (Elsevier, 2019)
Biological age (BA) is a construct that captures accelerated biological aging attributable to "wear and tear" from various exposures; we measured BA and weathering, defined as the difference between BA and chronological age, and their associations with race and psychosocial factors in a middle-aged bi-racial cohort. We used data from the Coronary Artery Risk in Young Adults study (CARDIA), conducted in 4 U.S. cities from 1985-2016 to examine weathering for adults aged 48-60 years. We estimated BA via the Klemera and Doubal method using selected biomarkers. We assessed overall and race-specific associations between weathering and psychosocial measures. For the 2694 participants included, Blacks had a BA (SD) that was 2.6 (11.8) years older than their chronological age while the average BA among Whites was 3.5 (10.0) years younger than their chronological age (Blacks weathered 6.1 years faster than Whites). Belonging to more social groups was associated with less weathering in Blacks but not Whites, and after multivariable adjustment, lower SES and more depressive symptoms were associated with more weathering among Blacks than among Whites. We confirmed racial differences in weathering, and newly documented that similar psychosocial factors may take a greater toll on the biological health of Blacks than Whites. Keywords: Biological age, Weathering, Psychosocial factors racial disparity